2021
DOI: 10.1111/padr.12444
|View full text |Cite
|
Sign up to set email alerts
|

Health Shocks, Recovery, and the First Thousand Days: The Effect of the Second World War on Height Growth in Japanese Children

Abstract: This article uses the health shock on Japanese civilians of the Second World War to understand the effects of health shocks at different developmental stages on children's long‐run growth pattern and to test whether recovery is possible after an early‐life health shock. We construct a prefecture‐level dataset of mean heights of boys and girls aged 6–19 from 1929 to 2015. Linking the heights recorded at different ages for the same birth cohort, we measure a counterfactual causal effect of the health shocks duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…They estimated that, in the absence of the famine, girls' mean age of menarche would have been 13.75 years. Finally, in Japan, an analysis of growth characteristics before, during, and after WWII (Schneider et al, 2021) revealed that the pubertal growth spurt occurred 0.51 and 0.46 years later for war-affected boys and girls, respectively. These trends could reflect the impact of resource scarcity on pubertal development, which is more likely to result in delayed puberty.…”
Section: Pubertal Development and War Exposurementioning
confidence: 99%
“…They estimated that, in the absence of the famine, girls' mean age of menarche would have been 13.75 years. Finally, in Japan, an analysis of growth characteristics before, during, and after WWII (Schneider et al, 2021) revealed that the pubertal growth spurt occurred 0.51 and 0.46 years later for war-affected boys and girls, respectively. These trends could reflect the impact of resource scarcity on pubertal development, which is more likely to result in delayed puberty.…”
Section: Pubertal Development and War Exposurementioning
confidence: 99%
“…Other studies examining menarche in relation to World War II focused on birth cohorts without directly measuring war exposures. These studies also tended to find delays in age at menarche, such as in Poland (Liczbińska et al, 2018), the Netherlands which focused on effects of the "Dutch Famine" (van Noord & Kaaks, 1991), and Japan (Schneider et al, 2021). These trends could reflect shifts toward energy-sparing phenotypes due to elevated energetic stress.…”
Section: Pubertal Development and War Exposurementioning
confidence: 99%